2000
DOI: 10.1063/1.481916
|View full text |Cite
|
Sign up to set email alerts
|

Homonuclear 3d transition-metal diatomics: A systematic density functional theory study

Abstract: The equilibrium bond lengths, harmonic vibrational frequencies, and dissociation energies of the ground state homonuclear 3d transition-metal diatomics (scandium through copper) were determined using six density functional or hybrid Hartree–Fock/density functional theory (HF/DFT) methods and unrestricted Hartree–Fock theory. Results are compared to other theoretical studies and to experimental values when available. The accuracy of the DFT results is found to be highly dependent upon the functional employed, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(111 citation statements)
references
References 91 publications
9
100
2
Order By: Relevance
“…They found that their theoretical results are dependent on the exchange-correlation (XC) functional used, suggesting that a systematic study is necessary to establish the best theoretical scheme as a requirement to gain basic knowledge of nanoparticle physicochemical properties. This remark is stressed by the results of comparative studies on first-row homonuclear TM dimers [17,18]. Several properties are calculated involving various XC functionals, which cast clear differences between each other in, for example, binding energies and equilibrium bond lengths.…”
Section: Introductionmentioning
confidence: 99%
“…They found that their theoretical results are dependent on the exchange-correlation (XC) functional used, suggesting that a systematic study is necessary to establish the best theoretical scheme as a requirement to gain basic knowledge of nanoparticle physicochemical properties. This remark is stressed by the results of comparative studies on first-row homonuclear TM dimers [17,18]. Several properties are calculated involving various XC functionals, which cast clear differences between each other in, for example, binding energies and equilibrium bond lengths.…”
Section: Introductionmentioning
confidence: 99%
“…On the theoretical side, there are a number of investigations spreading the level of the theory from an evolutive algorithm based on the semi-empirical Gupta potential [14], to a tight-binding molecular dynamics [15], and pseudo-atomic [16][17][18][19][20] and allelectron density functional theory (DFT) calculations [21][22][23][24]. The available results in the literature are not in good agreement.…”
Section: Introductionmentioning
confidence: 99%
“…A tradeoff between basis set size and active space size in early configuration interaction studies limited the accuracy of the relative energetics for the hundreds of states of various spins and symmetries considered [22,23]. Despite the need to reconsider the discrepancy between experimental and theoretical findings since the late 1970s, even recent comprehensive studies of transition metal diatomic molecules [24,27] continue to assume the 7 D u assignment to be the correct one for the ground state of iron dimer. There have, however, been some more recent high-level quantum chemistry calculations-multireference configuration interaction (MRCI) [28] as well as large basis set, single-reference coupled cluster [CCSD(T)] calculations [29]-which provide evidence for a more consistent alternative ground state 9 S À g for the iron dimer.…”
Section: Resultsmentioning
confidence: 99%